2019
DOI: 10.1242/dmm.039073
|View full text |Cite
|
Sign up to set email alerts
|

RDH10 function is necessary for spontaneous fetal mouth movement that facilitates palate shelf elevation

Abstract: Cleft palate is a common birth defect, occurring in approximately 1 in 1000 live births worldwide. Known etiological mechanisms of cleft palate include defects within developing palate shelf tissues, defects in mandibular growth and defects in spontaneous fetal mouth movement. Until now, experimental studies directly documenting fetal mouth immobility as an underlying cause of cleft palate have been limited to models lacking neurotransmission. This study extends the range of anomalies directly demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Dysphagia can occur in a Rdh10 mutant mouse embryo with defects in morphogenesis of pharyngeal skeletal elements and routing of pharyngeal motor nerves [ 45 ]. Dysphagia demonstrated as fetal mouth movement defects correlated with cleft palate in Rdh10 was confirmed through X-ray microtomography, in utero ultrasound video, ex vivo culture, and tissue staining.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysphagia can occur in a Rdh10 mutant mouse embryo with defects in morphogenesis of pharyngeal skeletal elements and routing of pharyngeal motor nerves [ 45 ]. Dysphagia demonstrated as fetal mouth movement defects correlated with cleft palate in Rdh10 was confirmed through X-ray microtomography, in utero ultrasound video, ex vivo culture, and tissue staining.…”
Section: Resultsmentioning
confidence: 99%
“…Increased risk in aspiration was reported in rats with experimentally induced pulmonary emphysema and pulmonary fibrosis [ 43 , 44 ]. Additionally, probability of dysphagia was also identified in Rdh10 mutant mice with cleft palate due to retinoid deficiency, TPH2 knockout (TPH -/- ) mice with serotonin (5-hydroxytryptamine [5-HT]) deficiency, and Uch-L1 gad /Uch-L3 Δ 3–7 double homozygous mice used as a neuro-degenerative animal model [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, double knockout of Raldh2 and Raldh3 resulted in severe craniofacial malformations including failure of frontonasal fusion (Halilagic et al, 2007), while knockout of Cyp26b1 prevented tongue depression and horizontal elevation of the palatal shelves (Okano et al, 2014). Upstream of these enzymes, knockout of Rdh10 demonstrated a role for RA synthesis in the spontaneous neuromuscular movement of the tongue and mandible, which facilitates palatal shelf elevation (Friedl et al, 2019). Thus, the cellular pool of RA must be tightly regulated for appropriate orofacial morphogenesis.…”
Section: Metabolism Of Folates and Retinoids In Orofacial Cleftsmentioning
confidence: 99%
“… 1 , 3 , 8 10 For the above reasons, and the fact that aglossia could also be accompanied by the normal palatogenesis, 11 , 12 some researchers considered that the tongue was not important in assisting palatal elevation. 5 However, some studies suggested that the lack of fetal tongue or mouth movement could also result in a delay in palatal elevation, 13 , 14 implying the positive role of tongue in palatal elevation. Irrespective of the hypothesis, the tongue plays an important role in palatal elevation due to its key location in the oral and nasal cavities.…”
Section: Introductionmentioning
confidence: 99%